2012
DOI: 10.1186/1471-2458-12-967
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of general obesity, abdominal obesity and related risk factors in urban adults from 33 communities of northeast china: the CHPSNE study

Abstract: BackgroundObesity increases the risk of many diseases. However, there has been little literature about the epidemiology of obesity classified by body mass index (BMI) or waist (abdominal obesity) among urban Chinese adults. This study is to fill the gap by assessing the prevalence of obesity and associated risk factors among urban Chinese adults.MethodsA representative sample of 25,196 urban adults aged 18 to 74 years in Northeast China was selected and measurements of height, weight and waist circumference (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
89
6
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 49 publications
15
89
6
14
Order By: Relevance
“…In Northeast China, a representative sample of 25,196 adults was evaluated. Analysis stratified by gender showed that men with a higher educational level, white-collar job, or cadre job were part of the high risk group, and women with a higher level of education or higher family income were in the low risk group [55]. Finally, in Brazil, a cross-sectional study with 1,720 Brazilian adults found results that point to the same direction.…”
Section: Prevalence Of Abdominal Obesitysupporting
confidence: 49%
“…In Northeast China, a representative sample of 25,196 adults was evaluated. Analysis stratified by gender showed that men with a higher educational level, white-collar job, or cadre job were part of the high risk group, and women with a higher level of education or higher family income were in the low risk group [55]. Finally, in Brazil, a cross-sectional study with 1,720 Brazilian adults found results that point to the same direction.…”
Section: Prevalence Of Abdominal Obesitysupporting
confidence: 49%
“…This present study's prevalence rate was, however, higher than the 12.2% reported among the general population in China [29]. The observed variations in these prevalence rates, however, appear to be more indicative of geographical disparities in the prevalence of abdominal obesity than population-based differences.…”
Section: Discussioncontrasting
confidence: 55%
“…12 With rapid economic development and urbanization over the past two decades, the lifestyle and diet in China have changed substantially, which in turn has increased the prevalence of cardiovascular diseases (CVD). 7 Several studies have reported a high prevalence of individual components of MetS such as obesity and hypertension in adults across urban areas of China; 13,14 however, the epidemiology of MetS in that population has not been fully explored. In addition, racial and ethnic differences are known to influence the prevalence and risk of MetS, and more recent definitions of MetS have tended to be ethnic-specific.…”
Section: Introductionmentioning
confidence: 99%